Mobile Marketing Studies: Review - Das, Jyotiranjan (International Journal of Psychosocial Rehabilitation, 2019)
The point of this paper is to clarify the principle class of portable showcasing research. It gives basic methodology about versatile promoting research design. The article means to feature the enormous territory of portable promoting examination and its requirement for additional comprehend the definition and marvel of versatile advertising. This exploration has noteworthy ramifications for understanding the field of order and focusing on computerized publicizing. This paper investigation concentrated on around forty-six chose diary distributions that are distributed somewhere in the range of 2010 and 2019. Rely upon the chose writing contemplated, the work on appropriation by shoppers concentrates just on a couple of regular zones. Specialists don't concur on the meaning of versatile advertising, conceptualization and portable showcasing marvel stay unexplained. This document discusses the mobile marketing concept and outlines its characteristics in comparison to traditional marketing channels. Next, researchers explore different approaches to mobile marketing and research findings relating to acceptance and attitudes and some of the most important theoretical approaches in this field. Two aspects of the acceptance process stand out: sensitivity and easy use. Finally, a number of suggestions are made for future mobile marketing research. The importance of this paper is that it provides the basic guidelines for researchers to concentrate on important areas in the field of mobile marketing and also allows practitioners to recognize the research pattern.